The science of ladder drills and plyometrics: Enhancing neuromuscular efficiency in athletes - Ravi, Pramod; K, Divya (Edelweiss Applied Science and Technology, 2024)
The objectives of this study are to determine whether there is any interaction between agility and athletic performance skills and plyometric training, ladder drill, and agility training; how different these effects are from one another; and how different the effects of low and high agility are from one another. The experimental methodology employed in this work uses a factorial analysis in 2x2. A population of 40 athletes, aged 15 to 17, were selected for the research sample using ordinal pairing. Devices that measure agility using the Illinois Agility Test. The following are the study’s findings: The post-test indicates a significant value of p < 0.05, indicating that the plyometric training technique, ladder drill, affects athletic performance skills (p > 0.05). Because the significance value indicates p of 0.006 < 0.05, there is a significant difference between the effects of low and high agility on athletic performance skills (p < 0.05). There is a significant (p > 0.05) interaction between agility (high and low), ladder drill training techniques, and plyometric training methods of athletic performance skills (p < 0.05). The findings indicate that following training, there is a relationship between agility and athletic performance abilities. According to the study, there is a connection between agility (high and low) and athletic performance skills, and agility has a major impact on athletic performance. Training techniques such as plyometric training and ladder drills are also related to agility. Applying the ladder drill and plyometric training techniques affects athletes’ performance abilities. It has been demonstrated that doing plyometric and ladder drills may enhance one’s athlete’s performance ability.